Assistance For MSMEs Halal Certification in Sukodono: Pendampingan Sertifikasi Halal UMKM di Sukodono - Fauji , Imam; Latifah, Fitri Nur; Anwar, Najih (Universitas Muhammadiyah Sidoarjo, 2022)
As an area adjacent to Surabaya of the provincial capital of East Java, Sukodono is certainly a densely populated area and the mobility of the population is very high, this fosters an entrepreneurial spirit for many residents there. MSMEs in Sukodono are very numerous and varied, for MSME activities in the food and beverage sector there are also very many so that the demand for guarantees for halal food products has become an important requirement there in accordance with law No. 33 of 2014 concerning Halal assurance. This community service activity aims to facilitate MSMEs engaged in food and beverage production to take care of halal certification as well as assist MSMEs in better business management, so that turnover and operating profits will increase. The method of this activity is carried out by lecturers assisted by FAI UMSIDA students, including initial assistance, implementation, mentoring and ongoing evaluation to obtain halal certification for SMEs